THE IMPACT OF GAMIFICATION ON STUDENT ENGAGEMENT AND RETENTION: INSIGHTS FROM A SYSTEMATIC LITERATURE REVIEW - Dewi, Siti Karunia; Khoiriyah, Malika; Aida, Nur; Aniyah, Aniyah; Surur, Miftahus (STKIP PGRI Situbondo, 2024)
In the digital era, technology in learning has become a fundamental need to improve the quality of teaching and learning. One innovative approach that can increase student motivation, engagement, and knowledge retention is learning gamification. This study aims to explore the impact of using gamification on student retention through the Systematic Literature Review (SLR) method. A total of 20 articles from scientific journals published in the 2020-2024 period were systematically analyzed based on journal quality criteria (Quality Assessment), including topic relevance, the impact of using gamification, and the correlation between gamification and student retention. The results of the analysis show that gamification positively affects student knowledge retention. So that teachers can develop learning by integrating gamification elements into learning to create a more enjoyable, competitive, and practical learning experience.